An Investigation of Optical Gain of Nanomaterial AlGaAsIn/InP under CTLSs in Optical Communications (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
The fundamental aim of this research paper has been to provide a critical role in the study of an investigation on optical gain enhancement of quaternary nanomaterial AlGaAsIn/InP under the CTLSs (Compressive Type Longitudinal Strains) in optical type telecommunication systems.
Keywords: Modal type gain intensity; Optical type gain intensity; CTLSs; AlGaAsIn; InP